An Overview on Gastroretentive Drug Delivery System - Chhetri, Himal Paudel; Thapa, Panna (Kathmandu University Journal of Science, Engineering and Technology, 2014)
Oral controlled release and site-specific drug delivery systems have been of great interest in the pharmaceutical field to achieve improved therapeutic advantage. Drug absorption in the gastrointestinal tract is a highly variable procedure, and prolonging gastric retention of the dosage form extends the time for drug absorption. Gastroretentive drug delivery systems are one such novel approach to prolong gastric residence time, thereby targeting site-specific drug release in the stomach for local or systemic effects. This approach is useful particularly for drugs which have a narrow absorption window in the upper part of the gastrointestinal tract. Various approaches of gastroretentive drug delivery systems, such as floating and non-floating, have been discussed in this review. Additionally, this review provides an overview of the merits, demerits, and evaluation parameters of gastroretentive systems.